2020
DOI: 10.1002/ags3.12392
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of one‐step nucleic acid amplification for the diagnosis of lymph node metastasis in colorectal cancer patients

Abstract: Generally, the postoperative examination of lymph nodes (LNs) is based on a microscopic examination of one hematoxylin and eosin (HE)‐stained slide; however, an examination of only one part of the LN might lead to incorrect staging of the tumor due to tissue allocation bias. Although multilevel sectioning and the use of immunohistochemistry (IHC) have improved the detection of micrometastases in LNs, this approach is laborious, time‐consuming, and costly. A novel molecular technique for the detection of LN met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In our previous published study[ 127 ], OSNA was superior to HE in identifying LNMs, with a false negative rate of 0% vs 44.4% and accuracy of 100% vs 76.4%, respectively (Table 2 ). As represented in Tables 2 and 3 , few studies evaluated HE and IHC, few performed multi-sliced tissue sections using HE and the remaining single slice HE tissue section vs OSNA[ 11 , 128 - 131 ]. While the detection of small metastatic foci in LNs is influenced by the skill and experience of the pathologists, the advantage of the OSNA assay is the possibility to perform standard evaluations without being influenced by operator skill or experience.…”
Section: Diagnostic Performance Of the Osna Assay In Crcmentioning
confidence: 99%
“…In our previous published study[ 127 ], OSNA was superior to HE in identifying LNMs, with a false negative rate of 0% vs 44.4% and accuracy of 100% vs 76.4%, respectively (Table 2 ). As represented in Tables 2 and 3 , few studies evaluated HE and IHC, few performed multi-sliced tissue sections using HE and the remaining single slice HE tissue section vs OSNA[ 11 , 128 - 131 ]. While the detection of small metastatic foci in LNs is influenced by the skill and experience of the pathologists, the advantage of the OSNA assay is the possibility to perform standard evaluations without being influenced by operator skill or experience.…”
Section: Diagnostic Performance Of the Osna Assay In Crcmentioning
confidence: 99%
“…In other words, application to chemotherapy depends on an incidental encounter of micrometastases. In this regard, OSNA takes advantage because it checks up a piece of LN as a bulk sample; thus, a stable detection ability will be warranted 41 . It should be emphasized that the OSNA assay provides a judgment performance equivalent to histopathological examination of three slices at a 2‐mm‐interval (Figure 1, Study 2).…”
Section: Can Micrometastases Be a Target For Adjuvant Chemotherapy?mentioning
confidence: 99%
“…In this regard, OSNA takes advantage because it checks up a piece of LN as a bulk sample; thus, a stable detection ability will be warranted. 41 It should be emphasized that the OSNA assay provides a judgment performance equivalent to histopathological examination of three slices at a 2‐mm‐interval (Figure 1 , Study 2). Thus, it is likely that OSNA test would contribute efficient detection of micrometastasis compared with the pathological routine survey with one slice.…”
Section: Can Micrometastases Be a Target For Adjuvant Chemotherapy?mentioning
confidence: 99%
“…The available scientific and clinical evidence, together with the mentioned characteristics, has introduced OSNA in current national and European clinical guidelines as an alternative technique for the determination of lymphatic involvement in breast cancer through SLN analysis [ 18 ]. Moreover, data available from studies in colorectal cancer demonstrated that OSNA is a valid technique for the detection of lymphatic involvement also in this cancer entity [ 19 ]. Hence, OSNA is now included in the recommendations for the determination of biomarkers in colorectal carcinoma [ 20 ].…”
Section: Introductionmentioning
confidence: 99%